PENERAPAN SANKSI PIDANA TERHADAP WAJIB PAJAK YANG MELAKUKAN TINDAK PIDANA PERPAJAKAN - Valentino Ohoiwirin; Ahmad Sholikhin Ruslie (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
The highest tax legal basis is Article 23A of the 1945 Constitution of the Republic of Indonesia was reads that "taxes and the other levies that are coercive for the state by law". Specifications for tax crimes and the mechanism for applying criminal sanctions. The tax system that uses a self-assessment system softens the coercive nature of this tax, with the prospect that people will fulfil their tax obligation properly. However, the problem that occurs is, on the contrary, it's a good system to use by the community to make deviations because people think that taxes are a burden that will reduce their income. So they do tax avoidance which aims to minimize the tax burden. The threat of criminal sanctions against tax crimes is quite heavy and clear. If both of them regulate criminal acts that "may cause losses to state revenues" or "may harm state finances or the state economy" and follow the principle of applying criminal law to laws governing criminal acts with the same object, they will be enforced. Law that specifically regulates the subject matter of the crime